AMOK – The most complex threat to hybrid public places - Solomun, Davor; Jozić, Marijan; Pišković, Damir (Crisis Management Days, 2025)
This paper analyzes and examines the specificities of police tactics in so-called AMOK situations (The state of uncontrolled rage or violence, often associated with insane destruction or attacks) characterized by extreme violence perpetrated by one or more individuals who randomly and uncontrollably endanger the lives and safety of people in specific circumstances within hybrid (quasi) public places. AMOK situations, due to their extremely negative impact on citizen safety, as well as public and national security, warrant special attention and obligate police and other security services to systematically monitor, as well as to follow crisis protocols for response and intervention. These crisis events are sudden and difficult to predict, involving the deadly use of firearms or bladed weapons. Recently, various motor vehicles have also been used, resulting in mass casualties and significant threats to the safety of public facilities and spaces. In evaluating the adequacy of police responses and tactics in resolving such situations, the key variable is the attackers – perpetrators who usually experience psychological difficulties, social isolation, and motivations linked to revenge, radical ideologies, terrorism, or personal frustrations, regardless of their social status. Victims are primarily located within hybrid public spaces, including students, passersby, employees, or visitors. The targets may be specific individuals and facilities, or the violence may be entirely random and arbitrary. AMOK situations typically progress through several stages: the preparatory phase, the execution phase, and the opposing phase, which includes intervention, neutralization of the attacker, and the post-crisis phase. It is important to emphasize that the quick reaction of potential victims, following the "RUN, FIGHT, or HIDE" strategy, along with efficient evacuation, is crucial until law enforcement arrives. Thus, within a dichotomous structure, this analysis not only provides a conceptual and theoretical framework but also includes a case study based on a sample of several (three to five) selected, typical AMOK incidents. These cases are analyzed according to a specially designed methodological pattern – a matrix comprising an optimal number (7–9) of variables, whose description facilitates the discussion of patterns and specificities of each case. The ultimate goal of this paper is to assess the effectiveness of applied police tactics based on the identified patterns of events and responses, with the assumption of validating and implementing best practices. These practices should not only address crisis resolution but also enhance preventive measures, ultimately strengthening public safety and mitigating the harmful consequences of such incidents.